PENGARUH SOCIAL COMPARISON TERHADAP KECEMASAN DALAM MENGHADAPI DUNIA KERJA PADA MAHASISWA FRESH GRADUATE PENGGUNA APLIKASI LINKEDIN - Dhea Nurfitri; Lilis Ratnasari (Jurnal Sosial Humaniora dan Pendidikan, 2024)
The Linkedin application is commonly used by job seekers, including fresh graduates. The use of the Linkedin application can make some users do social comparisons, so that they feel anxious. This study aims to test the effect of social comparison on anxiety in facing the world of work in fresh graduate students who use the Linkedin application. The method used is quantitative with a purposive sampling technique, a total of 250 research subjects. The measuring instrument used is an anxiety scale based on aspects of anxiety, while to measure the social comparison variable using the Iowa-Netherlands Comparison Orientation Measure (INCOM) scale based on the social comparison dimension. The results of the simple linear regression analysis showed an F value of 31,935 and a significance value of p = 0.000 (p ≤ 0.01) which is very significant. Based on the results of the analysis, the hypothesis is accepted, namely, there is a very significant influence between the influence of social comparison on anxiety in facing the world of work in fresh graduate students who use the Linkedin application with a contribution of 20.5%.